Decreasing NF-κB expression enhances odontoblastic differentiation and collagen expression in dental pulp stem cells exposed to inflammatory cytokines. - Neda S T Hozhabri; M Douglas Benson; Michael D Vu; Rinkesh H Patel; Rebecca M Martinez; Fatemeh N Nakhaie; Harry K W Kim; Venu G Varanasi (PLoS ONE)
Inflammatory response in the dental pulp can alter the collagen matrix formation by dental pulp stem cells and lead to a delay or poor healing of the pulp. This inflammatory response is mediated by cytokines, including interleukin-1β and tumor necrosis factor-α. In this study, it is hypothesized that suppressing the actions of these inflammatory cytokines by knocking down the activity of transcription factor Nuclear Factor-κB will lead to dental pulp stem cell differentiation into odontoblasts and the production of collagen. Here, the role of Nuclear Factor-κB signaling and its reduction was examined during odontogenic behavior in the presence of these cytokines. The results showed a significant increase in Nuclear Factor-κB gene expression and p65 protein expression by interleukin-1β and tumor necrosis factor-α. Nuclear Factor-κB activation in the presence of these cytokines decreased significantly in a dose-dependent manner by a Nuclear Factor-κB inhibitor (MG132) and p65 siRNA. Down-regulation of Nuclear Factor-κB activity also enhanced the gene expression of the odontoblastic markers (dentin sialophosphoprotein, Nestin, and alkaline phosphatase) and displayed an odontoblastic cell morphology indicating the promotion of odontogenic differentiation of dental pulp stem cells. Finally, dental pulp stem cells exposed to reduced Nuclear Factor-κB activity resulted in a significant increase in collagen (I)-α1 expression in the presence of these cytokines. In conclusion, a decrease in Nuclear Factor-κB in dental pulp stem cells in the presence of inflammatory cytokines enhanced odontoblastic differentiation and collagen matrix formation.